Computational analysis for fractional model of coupled Whitham-Broer-Kaup equation - Jagdev Singh; Arpita Gupta; Dumitru Baleanu (Alexandria Engineering Journal)
In this research paper, we study a semi analytical technique to solve the nonlinear partial differential equations. This technique is good combination of homotopy analysis method with Kharrat-Toma transform. Also, we present the numerical solution of nonlinear fractional coupled Whitham-Broer-Kaup equation using studied technique. The Whitham-Broer-Kaup model is broadly considered to study the tsunami wave dynamics under gravity. The regularized version of Hilfer-Prabhakar fractional derivative is used to model the problem. Some qualitative properties, existence and uniqueness of the considered model and its solution are also discussed.The obtained solutions are presented graphically to show the efficiency of studied technique. Error analysis tables are also given to demonstrate the accuracy of obtained results.